Health at a Glance : Latin America and the Caribbean 2020 - OECD; World Bank (Paris: OECD Publishing, 2021)
This report presents key indicators on health and health systems in 33 Latin America and the Caribbean countries. This first Health at a Glance publication to cover the Latin America and the Caribbean region was prepared jointly by OECD and the World Bank. Analysis is based on the latest comparable data across almost 100 indicators including equity, health status, determinants of health, health care resources and utilisation, health expenditure and financing, and quality of care. The editorial discusses the main challenges for the region brought by the COVID‑19 pandemic, such as managing the outbreak as well as mobilising adequate resources and using them efficiently to ensure an effective response to the epidemic. An initial chapter summarises the comparative performance of countries before the crisis, followed by a special chapter about addressing wasteful health spending that is either ineffective or does not lead to improvement in health outcomes so that to direct saved resources where they are urgently needed.